Effects of bilateral knee arthroplasty on sagittal spinopelvic balance in patients with primer degenerative osteoarthritis (Annals of Medical Research, 2021)
Aim: We aimed to evaluate the change in sagittal spinopelvic parameters in knee osteoarthritis patients without prior degenerative spinal disease following bilateral knee arthroplasty. Knee osteoarthritis often causes knee flexion contracture and the flexion contracture may affect posture and lumbar lordosis.Material and Methods: We performed a retrospective study by evaluating the records of patients who have undergone bilateral knee arthroplasty in our clinic between 2012 and 2016 in patients due to degenerative bilateral knee osteoarthritis and minimum 12 months follow up. Patients with prior hip surgery, prior spine surgery, rheumatic disease and postoperative flexion contracture were excluded. Lumber lordosis, sacral slope, pelvic tilt and pelvic incidence were measured on lateral lumbosacral view in supine position pre-postoperatively and compared with paired T test. Extension deficit was also measured preoperatively.Results: This study includes 83 patients (77 females and 6 males) who underwent bilateral knee arthroplasty and matched the inclusion and exclusion criteria. The average age at the time of first total knee arthroplasty was 64.4 years. Mean follow up was 37.3(12-66) months. The mean lumber lordosis was 43.9° preoperatively and 49.6° postoperatively. The increase in lumbar lordosis angle was statistically significant (p: 0,001). These changes were only related to the degree of extension deficit but not to age and postoperative follow-up time. Sacral slope, pelvic incidence and pelvic tilt did not change significantly. Conclusion: Bilateral knee arthroplasty increased lumbar lordosis patients with primer degenerative osteoarthritis especially who had high extension deficit. Sacral slope and pelvic tilt were decreased postoperatively but not significantly changed.
Keywords: Lumbar lordosis; bilateral knee arthroplasty; knee-spine; primer osteoarthritis; extension deficit